2018
DOI: 10.1111/cob.12290
|View full text |Cite
|
Sign up to set email alerts
|

Mental health quality of life after bariatric surgery: A systematic review and meta‐analysis of randomized clinical trials

Abstract: Recent literature has raised concerns regarding the risk of adverse psychiatric events among bariatric surgery patients. However, the relationship between weight loss therapy and psychiatric outcomes is confounded by baseline psychosocial characteristics in observational studies. To understand the impact of bariatric surgery on the risk of adverse mental health outcomes, we conducted a systematic review and meta‐analysis of randomized controlled trials that compared surgical and non‐surgical treatments and ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
34
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 53 publications
5
34
1
1
Order By: Relevance
“…Notably, prior to undergoing bariatric surgery, the MCS scores among both the patient group with Medicaid and the patient group with commercial insurance were at or near the US population norm. These findings generally align with those of other research on mental HRQOL among patients undergoing bariatric surgery: obesity has little impact on mental HRQOL .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Notably, prior to undergoing bariatric surgery, the MCS scores among both the patient group with Medicaid and the patient group with commercial insurance were at or near the US population norm. These findings generally align with those of other research on mental HRQOL among patients undergoing bariatric surgery: obesity has little impact on mental HRQOL .…”
Section: Discussionsupporting
confidence: 88%
“…Findings among the general patient population align with the current study’s findings; a recent meta‐analysis reported that bariatric surgery had a greater positive influence on physical HRQOL compared with mental HRQOL across 72 studies . Similarly, a second meta‐analysis found no effect of surgery on mental HRQOL following bariatric surgery among 11 randomized clinical trials, findings which also align with the current study’s report . Our findings support reporting group‐specific changes following bariatric surgery, as reporting overall findings may mask important policy‐relevant and clinically relevant differences.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Quality of life is a multidimensional construct composed of physical and mental components, yet bariatric surgery has a much greater impact on physical than mental quality of life . In fact, a recent meta‐analysis concluded that bariatric surgery does not improve short‐ or long‐term mental quality of life compared with nonsurgical interventions for obesity . Psychosocial factors, such as psychological comorbidities and various forms of disordered eating, impact mental quality of life .…”
Section: Introductionmentioning
confidence: 99%
“…4 In fact, a recent meta-analysis concluded that bariatric surgery does not improve short-or long-term mental quality of life compared with nonsurgical interventions for obesity. 18 Psychosocial factors, such as psychological comorbidities and various forms of disordered eating, impact mental quality of life. 7 Thus, improving psychosocial functioning is important in its own right because it reduces psychological distress and enhances well-being.…”
mentioning
confidence: 99%